PERHITUNGAN NILAI EKONOMI SUMBERDAYA TERUMBU KARANG BERDASARKAN WILLINGNESS TO DONATE (WTD) WISATAWAN BAHARI DI TAMAN NASIONAL KARIMUNJAWA - Amalia Febryane Adhani Mazaya; Fredinan Yulianda; Taryono Taryono (Universitas Pattimura, 2023)
Karimunjawa National Park (TNKJ) as one of the seven marine national parks is priority for marine management. Ecosystems that contribute a lot of indirect value is coral reef ecosystems. Its utilization for marine tourism activities has enormous potential but is also vulnerable to damage. Calculation of economic value is carried out as basic information on tourist willingness in terms of coral reef conservation through a Willingness to Donate (WTD) that it can be used as one of the inputs for sustainable management. The research was conducted in the main waters of the TNKJ marine tourism utilization zone in August-September 2017. Tourist data collection was carried out through structured questionnaire with 45 selected respondents. The results show tourists who use coral reef ecosystems snorkel as many as 4755 people peryear and 853 people dive peryear in an area of ​​886,302.7841 m2. The average WTD for snorkeling tourists is IDR206,250 and IDR87,500 for diving tourists. The total cost of rehabilitation of coral reefs per year is IDR1,055,356,250 per year. The resulting value can be used as a reference for the cost of repairing damaged ecosystems, responsible marine tourism activities and as an alternative priority incentive for coral reef conservation activities in TNKJ.